2024
DOI: 10.3390/nu16060777
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Role of Recreational Physical Activity in the Relationship between the Dietary Intake of Live Microbes and the Systemic Immune-Inflammation Index: A Real-World Cross-Sectional Study

Yanwei You,
Yuquan Chen,
Mengxian Wei
et al.

Abstract: The main topic of this research is the relationship between dietary intake of live microbe-containing (LMC) foods, recreational physical activity (RPA), and the systemic immune-inflammation index (SII). This study presented a cohort of 26,254 individuals in the National Health and Nutrition Examination Survey (NHANES), representing an estimated weighted population of 193,637,615 in the United States. Weighted multivariable linear regression models were used in consideration of the multi-stage sampling design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The previous studies found that moderate-to-vigorous physical activity, but not sedentary behavior, were independently related to reduced odds of elevated CRP 45 , 46 , which was consistent with results in the current study. In addition, more time spent in recreational physical activity was found to be negatively associated with the SII in the NHANES cohort of 26,254 participants 47 . In a randomized controlled trial, patients with childhood cancer undergoing treatment who received 6–8 weeks of supervised exercise intervention had significantly lower SII compared to controls 48 .…”
Section: Discussionmentioning
confidence: 89%
“…The previous studies found that moderate-to-vigorous physical activity, but not sedentary behavior, were independently related to reduced odds of elevated CRP 45 , 46 , which was consistent with results in the current study. In addition, more time spent in recreational physical activity was found to be negatively associated with the SII in the NHANES cohort of 26,254 participants 47 . In a randomized controlled trial, patients with childhood cancer undergoing treatment who received 6–8 weeks of supervised exercise intervention had significantly lower SII compared to controls 48 .…”
Section: Discussionmentioning
confidence: 89%
“…In BPPV, the detachment and displacement of otoliths can mechanically stimulate the semicircular canal's ampullary ridge, leading to vertigo (23,24). Regarding the potential mechanisms, some researchers believe that dysfunction in the central nervous system (CNS) increases the excitability of the trigeminal caudate nucleus, solitary tract nucleus, and vestibular nucleus, resulting in vertigo (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The computation of the SII level hinges upon the following formula: (platelet count × neutrophils count)/lymphocytes count. 32 , 33 , 34 , 35 Referring to previous literature, 36 SII was set as a categorical variable according to the mean value.…”
Section: Methodsmentioning
confidence: 99%